Persistence of a Stx-Encoding Bacteriophage in Minced Meat Investigated by Application of an Improved DNA Extraction Method and Digital Droplet PCR - Spilsberg, B.; Sekse, C.; Urdahl, Anne M.; Nesse, Live L.; Johannessen, Gro S. (Frontiers in Microbiology, 2021)
Shiga toxin-producing E. coli (STEC) are important food-borne pathogens with Shiga toxins as the main virulence factor. Shiga toxins are encoded on Shiga toxin-converting bacteriophages (Stx phages). Stx phages may exist as free bacteriophages in the environment or in foods, or in the lysogenic state where they are integrated into the host genome. From a food safety perspective it is important to have knowledge on the survival and persistence of Stx phages in food products since these may be integrated in bacterial hosts through transduction if conditions are right. Here, we present the results from a study investigating the survival of a Stx phage in minced meat from beef stored at slight abuse temperature (8°C) along with modification and optimisation of the methods applied. Minced meat from beef were inoculated with known levels of a labelled Stx phage prior storage. Phage filtrates were used for plaque assays and DNA extraction, followed by qPCR and ddPCR. The results from the pilot study suggested that the initial DNA extraction protocol was not optimal and several modifications were tested before a final protocol were defined. The final DNA extraction protocol comprised ultra-centrifugation of the whole phage filtrate for concentrating the phages and two times phenol-chloroform extraction. The protocol were used for two spiking experiments. The DNA extraction protocol resulted in flexibility in the amount of DNA available for use in PCR analyses, ultimately increasing the sensitivity of the method used for quantification of phages in a sample. All three quantification methods employed showed similar trends in the development of the phages during storage, where ddPCR have the benefit of giving absolute quantification of DNA copies in a simple experimental setup. The results indicate that the Stx phage persist and remain infectious for at least 20 days under the storage conditions used in the present study. Although it is less likely that transduction will take place at 8°C with subsequent forming of STEC, such events might take place at later stages when conditions are more optimal, thus representing a potential health risk for humans.